SYT6 associates with components of the plant autophagy machinery - Cardeñas Echevarría, Carlos; Moya-Barrientos, Miriam; Sánchez-Vera, Victoria; Ruiz-López, Noemí (2026)
Membrane contact sites (MCSs) are fundamental hubs of inter-organelle communication, mediating the non-vesicular transfer of lipids, ions, and metabolites to maintain cellular homeostasis. Synaptotagmins (SYTs) are membrane-bridging proteins that facilitate lipid exchange at these sites. Particularly, SYT6, an endoplasmic reticulum (ER)-anchored protein, has been proposed to localize at ER-trans-Golgi network (TGN) contact sites, although its role is not yet known. Our preliminary experiments have indicated that SYT6 putatively associates with ATG18a, suggesting a potential link to the autophagy machinery. To investigate this, we transiently co-expressed SYT6 with either ATG8a or ATG18a in Nicotiana benthamiana leaves and analyzed interactions using Bimolecular Fluorescence Complementation (BiFC) and co-inmunoprecipitation (Co-IP). BiFC images were quantified using an AI-based segmentation pipeline (Ilastik) and Fiji. The results confirmed subcellular proximity of SYT6 to both ATG8a and ATG18a in vesicular structures, with distinct patterns: SYT6–ATG8a vesicles were significantly smaller (0–10 µm2) and more numerous, whereas SYT6–ATG18a complexes formed larger structures (often >50 µm2). Co-IP further validated the specific physical association of SYT6 with both autophagy proteins. These findings support that SYT6 physically associates with key components of the autophagy machinery and suggest it may play distinct roles at different stages of autophagosome formation, potentially linking ER membranes to autophagic vesicles. Reference: - Huercano, C., Moya-Barrientos, M., Cuevas, O., Cardenas, C., Salas, J. J., Sanchez-Vera, V., & Ruiz-Lopez, N. (2025). The plant lipid contactome: emerging roles of inter-organelle contact sites in lipid metabolism. Progress in lipid research, 101, 101372. Advance online publication. https://doi.org/10.1016/j.plipres.2025.101372 Acknowledgements: Supported by project PID2024-159647NB-I00 and MICIU fellowship FPU24/01639. We thank the Dept. of Molecular Biology and Biochemistry (UMA) and our research group.
Keywords: Proteínas vegetales; Solanáceas; Autophagy; SYT6; Membrane contact sites; Endoplasmic reticulum